The Hidden Aspects of Academic Assessment and its Unintended Outcomes…: the Perspective of Students - Pauluk, Dorota (Annales Universitatis Paedagogicae Cracoviensis. Studia ad Didacticam Scientiarum Socialium Pertinentia, 2020)
The aim of this article is to describe the hidden aspects of the academic assessment system and the unintended outcomes. In official curricula, academic teachers include an assessment system which contains, among others, methods, criteria for verifying knowledge and skills, requirements needed to obtain a certain degree and examination conditions. The results of research on the hidden curriculum show that various elements of this system lead to many unintended consequences. Assessment is embedded in a broad educational context, and the elements of the educational process and assessment enter into mutual relations. Moreover, the implementation of planned assessment elements by teachers is always connected with errors and irregularities. Students are constantly evaluated and so they experience the unintended outcomes of this evaluation on a daily basis. Based on my own study - a qualitative analysis of the content of free statements of pedagogy students at one of Poland’s universities - certain shortcomings, inconsistencies and gaps in the scope of assessment as perceived from their perspective have been identified. Based on their subjective experience related to assessment, research participants discovered the unintended outcomes of assessment. They concerned, inter alia, their approaches to academic knowledge, learning, coping strategies and peer relations.